A study on common complaints towards the public bus driver attitude / Ahmad Shahrizat Amrin and Constantine Lester L. Abbie - Amrin, Ahamd Shahrizat; L. Abbie, Constantine Lester (2013)
Public bus driver attitude are the main problems that not been taken to the authority since there are no one's come to overcome these problems. The attitude of public bus driver is something that everybody missed to overcome because it such mixed with the culture and attitude. This problem happened in everywhere and in Sabah we have no other cheap fair transport beside bus so this make these happened because people have none option to make. The drivers tend to be rude and recklessly on the way, it endangered all passengers in the bus and mostly public buses in Sabah only depart after all of the capacity load or loaded. The significance of the study is i f we know the main complaints about attitude of busses drivers, the information can be used as feedback to relevant bodies such as bus association and the authority. Towards this research we had focus on several parts, courses and campuses as our participant which is from Administration, Business and Medical. A l l of them are categories to senior and junior and divided to public and private institution, our focus is only to identify for their common complaint toward public bus driver attitude.